Objectivity and accountability in migration control using risk assessment tools - Dekkers, Tim (European journal of criminology, 2019)
In recent years immigration control has seen an increase in the implementation of risk assessment technology. According to proponents, such technologies would lead to more objective decision-making compared with the discretionary decisions made by street-level bureaucrats. However, because empirical research on risk assessment technology is limited, it is not quite clear how risk assessment technology in migration control impacts the decision-making process and to what extent it does make the decision-making process more objective. This article aims to shine a light on this issue by making use of a case study of Amigo-boras, a smart camera system used by the Royal Netherlands Marechaussee (RNM) for migration control purposes. Qualitative data show that Dutch immigration officers are still able to exercise discretion in the execution of their tasks, placing doubt on claims to objectivity. This finding is confirmed in quantitative data based on a US case study. Although quantitative data on the decision-making process would be able to show if these doubts were justified, the RNM has no such data on the outcomes and selection process using Amigo-boras. This information gap raises new issues regarding the objectivity of the selection process and the individual accountability of RNM officers.